Fipronil exposure alters oxidative stress responses of Nile tilapia (Oreochromis niloticus) to acute moderate hypoxia - Dourado, Priscila Leocádia Rosa [UNESP] (2025)
Acute hypoxia is known to increase the generation of reactive oxygen species (ROS), leading to modulation in antioxidant defenses. Pollutant exposure can potentiate ROS generation during hypoxic events and impair antioxidant defenses, increasing the susceptibility of hypoxia-tolerant fishes, such as the Nile tilapia (Oreochromis niloticus), to oxidative stress. The purpose of this study was to evaluate oxidative stress responses of O. niloticus to acute (3 and 8 h) moderate hypoxia (dissolved oxygen ≤2 mg/L−1) and how these responses are affected by simultaneous exposure to the insecticide fipronil (0.1 and 0.5 µg L−1). Hypoxia exposure for 3 h caused an increase in glutathione peroxidase (GPx) activity in the gill and also increased catalase (CAT) and glutathione S-transferase (GST) activities in the liver. After 8 h of hypoxia, glutathione reductase (GR) activity increased. DNA damage (comet assay) in erythrocytes was reduced by hypoxia after 3 and 8 h. Fipronil exposure for 3 h decreased CAT activity in the gill, both under normoxia and hypoxia. After 8 h, the combination of fipronil and hypoxia increased GR activity in the gill. In the liver, fipronil exposure under hypoxia for 3 h increased CAT and GR activities; after 8 h, CAT was decreased, and GST increased. GR was also increased by fipronil under normoxia for 8 h. All treatments reduced lipid peroxidation levels in the gills, but in the liver, lipid peroxidation was increased by fipronil after 3 h under normoxia. Moreover, fipronil exposure under hypoxia for 3 and 8 h increased DNA damage in erythrocytes, while 8 h of fipronil exposure under normoxia decreased it, suggesting the activation of DNA repair mechanisms. Results show that both fipronil and hypoxia exposure significantly modulate the oxidative stress parameters of O. niloticus and that the combination of these factors produces more pronounced effects.